(untitled) (Bangladesh Journal of Public Administration, 2021)
Within urbanized areas, the importance of neighborhood ponds should be assessed and investigated with its socio-spatial parameters (access and linkage, sociability, uses and activities, comfort and image etc) since such water bodies act as retention basin during floods, reservoir for lean period and responsive socializing agent to measure community interaction which are generally been neglected by city government, threatened by developers but taken care by neighborhood people in Old Dhaka. Most of the inner city small neighborhoods ponds have been encroached and filled up upon demand on land as the pond were not integrated in the city planning. The main objective of this research is to assess the significance of such water bodies and revive the spatial relationship of neighborhood ponds with its nearby residents. Therefore a socio-environmental survey (quantitative and qualitative) is held on neglected and threatened small neighborhood ponds of Old Dhaka with direct observation, in-depth interviews of the residents to compare the environmental, ecological and social contexts and explore the opportunities. An integrated assessment for enhancing sustainability and creating opportunities through community participation has been suggested to rejuvenate the ponds with attention for wetland preservation and to integrate into community development programs or planning.